Exposure, perceived risk, and psychological distress among general population during the COVID-19 lockdown in Wuhan, China - Liu, Yujun; Liu, Linping; Shi, Zhilei (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic that has been going on since the end of 2019 impacts people on both the physical and psychological level. However, the psychological status, especially its underlying psychosocial mechanisms among general population in Wuhan, the earliest epicenter and hardest-hit city in China during the pandemic, have not been well investigated. This study aimed to examine the relationships between exposures, perceived risk and psychological distress among general population in Wuhan during the COVID-19 lockdown. Data was from a cross-sectional online survey conducted from 20th February to 4th March in 2020. Final analyses included 4234 Wuhan respondents. 5-item Hopkins Symptom Checklist was adopted to assess respondents’ psychological distress. It was found that nervousness, fear and worry were the most common symptoms among Wuhan residents during the lockdown. Exposure within close physical distance, exposure within social network and perceived risk significantly positively related to respondents’ psychological distress. Moreover, perceived risk mediated the effects of exposures on respondents’ psychological condition. These findings conduce to identify the populations at higher risk of suffering the psychological disturbance during the pandemic, and are expected to inform the policy makers and mental health professionals to monitor and improve perception of risk among target population by appropriate interventions.